Cytotoxic effects of juglone and Pterocarya fraxinifolia on prostate cancer cells - Morteza Mahdavi; Mohammad Azadbakht; Akbar Vahdati; Mohammad Shokrzadeh; Ayub Farhadi (Wolters Kluwer Medknow Publications, 2019)
Aim: Juglone with naphthoquinone structure has medicinal properties and its anticarcinogenic and antioxidant effects have been proven. In this research, the cytotoxic and apoptosis effects of juglone and Pterocarya fraxinifolia (PF) methanolic extract on human prostate cancer cells were studied. Materials and Methods: The PC3 and DU145 human cancer cells and normal cells of primary prostate epithelial cells (ATCC PCS-440-010) were treated with juglone and PF extract at the concentrations of 10, 50, 100, 500, and 1000 μg/mL for 24, 48, 72, and 96h. The morphological changes were examined by reversed microscope. The survival percentage of cell lines was evaluated by MTT (3,4,5-dimethylthiazole-2-yl-2,5-diphenyltetrazolium bromide) test. The rate of apoptosis and expression of AR and CLU genes were examined by flow cytometry and real-time polymerase chain reaction. Results: All concentrations after 24h caused morphological changes in PC3 and DU145 cells, and these changes were intensified after 48, 72, and 96h. Also, concentrations of 100 and 500 μg/mL caused morphological changes in normal cells. The results of MTT test showed a significant decrease in PC3 and DU145 cell survival rate at 50, 100, and 500 μg/mL concentrations (P < 0.05). Juglone at 10 μg/mL concentration induced apoptosis in cancer cell lines. Conclusion: Juglone and PF could decrease the growth of cancer cell lines through the mitochondrial pathway. So PF could be considered as a potential candidate for therapeutic herbal medicine in treating cancers.